2016
DOI: 10.1074/jbc.m115.713552
|View full text |Cite
|
Sign up to set email alerts
|

Templated Aggregation of TAR DNA-binding Protein of 43 kDa (TDP-43) by Seeding with TDP-43 Peptide Fibrils

Abstract: Frontotemporal lobar degeneration (FTLD)2 is the second most common dementing disorder in patients under 65 years of age and is characterized by progressive atrophy of the frontal and temporal lobes in the brain. Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive motor neuron degeneration. In 2006, TAR DNA-binding protein of 43 kDa (TDP-43) was identified as the major component of tau-negative, ubiquitin-positive inclusions in these diseases (1, 2). TDP-43 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 33 publications
3
89
0
Order By: Relevance
“…Interestingly, seeded aggregation required the interaction of the peptide seed with the identical peptide sequence of the host protein (Shimonaka et al . ). This indicates, that conformation‐specific templating of TDP‐43 can lead to differentially misfolded conformers, which furthermore can cause different patterns of pathology and disease phenotypes in a strain‐like manner.…”
Section: Multiple Conformations Of Pathogenic Protein Assemblies May mentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, seeded aggregation required the interaction of the peptide seed with the identical peptide sequence of the host protein (Shimonaka et al . ). This indicates, that conformation‐specific templating of TDP‐43 can lead to differentially misfolded conformers, which furthermore can cause different patterns of pathology and disease phenotypes in a strain‐like manner.…”
Section: Multiple Conformations Of Pathogenic Protein Assemblies May mentioning
confidence: 97%
“…; Shimonaka et al . ), which can cluster together in large complexes with resemblance to pathological inclusions (Fang et al . ).…”
Section: Evidence For Prion‐like Behavior Of Ftd‐associated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This propensity has been localised to a low-complexity domain in the C-terminal region that may play a role in RNA binding, granule formation, and/or liquid–liquid phase separation to subserve transcription dynamics and mRNA transport [6, 12, 32, 34, 55, 56]. It is hypothesised that inherited or spontaneous mutation of the encoding gene, TARDBP , or of an interacting partner, upsets the balance between aggregation and dissolution of TDP-43 [14, 71], which may be differentially regulated under changing conditions, including during the cellular stress/death response [7, 30].…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, it was observed that TDP-43 fibrils formed from short C-terminal derived peptides triggered the seeddependent aggregation of wild type TDP-43 (TDP-43 WT ) or TDP-43 lacking a nuclear localization signal in SH-SY5Y cells resulting in different peptides sequences of TDP-43 producing fibrils with distinct biochemical properties reminiscent of prion strains. 12 Recently a novel method for quantifying protein inclusions was described. 13 We reasoned that this method might be used to provide a quick and robust measure of prion-like propagation.…”
Section: Introductionmentioning
confidence: 99%